(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cartography has been impacted by advancement of data and correspondence innovations and topographical reasoning. The most grounded and most unmistakable contemporary streams in cartography and geographic data frameworks are the presence and utilization of Web 2.0, which bolsters Web-based administrations for some individuals all around the globe and quick advancement of group sourcing permitting accumulation of obstinate data.